Asian Rhinoplasty Techniques - Bergeron, Léonard (Thieme Medical Publishers, 2009)
Asian rhinoplasty is a broad term that refers to a set of rhinoplasty techniques commonly used in Asian populations. Although these techniques are well developed and documented in Asian languages, there are relatively few English-language articles on the subject, and even fewer on current debates and controversies among plastic surgeons. Knowledge of these different techniques is essential to perform an adequate rhinoplasty in Asians. For Western patients, reduction rhinoplasty with dorsal hump rasping and lower lateral cartilage resection is classic. In contrast, silicone implant augmentation rhinoplasty is the most commonly used technique in Orientals. This article focuses on current rhinoplasty practices and controversies in Asia. It reviews morphologic differences between the Oriental and Western noses, as well as common patient requests. Polytetrafluoroethylene (Gore-Tex) and silicone implant augmentation are discussed. A new augmentation rhinoplasty with diced cartilage is described in more detail.